The Role Of Parents In Managing Children’s Pocket Money : A Case Study Of Students’ Guardians In Depok City: Role Of Parents In Managing Children’s Pocket Money : A Case Study Of Students’ Guardians In Depok City - Madsari, Makhmudah; Suhud, Usep; Wibowo, Agus (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study aims to evaluate and explore the concept of parents in managing children’s pocket money, especially among elementary school guardians in Depok city. The main focus of this study is to understand how parents aged 30 to 45 years manage and educate their children about pocket money management. One important aspect that needs to be considered is financial literacy, which is knowledge that helps individuals understand the source of money, allocation, and making wise choices in spending. By teaching children about pocket money management, parents can equip them with useful skills for the future. The methodology of this study uses a qualitative approach, through interviews and surveys, to explore the experiences and views of parents. This study involved 101 parents with the characteristics of elementary school guardians in Depok, aged 30-55 years. Data were collected through an online survey, and data analysis was carried out using the content analysis method for the topic of children’s pocket money management. The results of the study are expected to provide in-depth insights into pocket money management strategies implemented by parents, the challenges faced, and the importance of financial literacy in educating children to become wise financial managers in the future.